The nitrogen footprint and reactive nitrogen reduction potential of cotton production in China. (20th May 2023) - Huang, Weibin; Wu, Fengqi; Zhang, Zhenggui; Meng, Yongming; Wang, Jian; Li, Qinqin; Han, Yingchun; Feng, Lu; Li, Xiaofei; Wang, Guoping; Lei, Yaping; Fan, Zhengyi; et al.
Abstract: Analyzing the nitrogen footprint (NF) and the potential reduction of reactive nitrogen in crop production and proposing higher N utilization efficiency strategies are important approaches to sustainable crop development. Cotton is an important cash crop in China. However, only a few studies have systematically quantified the NF of cotton production in China, analyzed its temporal and spatial varieties, clarified its main constituent factors and influential factors, and explored its nitrogen emission reduction potential. This study adopts the life cycle method and analyzes the temporal-spatial varieties in the NF of cotton production in China's main cotton planting areas from 2004 to 2018 based on statistical data, analyzes the main components of the nitrogen footprint of China's cotton production, studies the main driving factors of China's cotton nitrogen emissions based on principal component analysis, simulates the nitrogen emissions of China's cotton production combined with the STIRPAT model, and comprehensively analyzes the potential nitrogen emission reduction of China's cotton production. The results indicated that the average nitrogen footprint per unit area (NFa) of cotton planting districts in Northwest China (Nw.CPD), the Yellow River Basin (Yel.RCPD) and the Yangtze River Basin (Yan.RCPD) was 112 kg Neq·ha −1, 65 kg Neq·ha −1 and 155 kg Neq·ha −1, respectively, and the NFa of cotton production in Hunan was the highest. In terms of spatial distribution, the NFa, NFy and NFv of cotton production in Yan.RCPD were higher than those in Yel.RCPD and Nw.CPD, and the NF of cotton planted in Yel.RCPD was the lowest. The NFa of cotton planting in China increased continuously, and the NFa in Nw.CPD showed an increasing trend, while the NFa in Yel.RCPD and Yan.RCPD showed a decreasing trend. Principal component analysis (PCA) showed that fertilizer and the associated reactive nitrogen losses were the main components of the nitrogen footprint. The prediction results of the STIRPAT model showed that compared with 2018, China's cotton production can reduce nitrogen emissions by 54.43 kilotons in 2050 at most. Improved fertilizer utilization efficiency, optimized field management measures and effective policy intervention are effective strategies to reduce the nitrogen footprint of cotton production. Graphical abstract: Image 1 Highlights: From 2004 to 2018, China's cotton production NFa increased, with an average annual increase of 1.168 kg Neq·ha −1 . Fertilizer and its losses are the main components of cotton nitrogen footprint in China. STIRPAT model predicts China's cotton production can reduce nitrogen emissions by 54.43 kilotons at the most in 2050. Improving fertilizer use efficiency and introducing effective policy can reduce nitrogen footprint of cotton production.